2018
DOI: 10.1038/s41598-018-24152-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA-release by Streptococcus pneumoniae autolysin LytA induced Krueppel-like factor 4 expression in macrophages

Abstract: The recruitment of myeloid cells to the lung is of utmost importance for the elimination of invading pathogens. We investigated the Streptococcus pneumoniae-dependent induction mechanism of KLF4 in macrophages as a potential regulator of the macrophage immune response. We demonstrated that only viable pneumococci, which have direct contact to the host cells and release LytA-dependent DNA, induced KLF4. Exogenous supplementation of pneumococcal, other bacterial, eukaryotic foreign (human) or self (mouse) DNA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…10. Further, unlike in epithelial cells, there is no induction of KLF4 with bacterial DNA alone 136 but the signal was partly back when the cells were stimulated with the combination of pneumococcal strain R6x∆lytA and bacterial DNA, the inducing factor for KLF4 in macrophages 169 . It has been reported that S. pneumoniae autolysin LytA (N-acetylmuramoyl-L-alanine amidase) activates immunomodulatory signaling pathways in macrophages by releasing bacterial cell wall constituents such as peptidoglycan and diconic acid 187 .…”
Section: In Vitromentioning
confidence: 96%
See 2 more Smart Citations
“…10. Further, unlike in epithelial cells, there is no induction of KLF4 with bacterial DNA alone 136 but the signal was partly back when the cells were stimulated with the combination of pneumococcal strain R6x∆lytA and bacterial DNA, the inducing factor for KLF4 in macrophages 169 . It has been reported that S. pneumoniae autolysin LytA (N-acetylmuramoyl-L-alanine amidase) activates immunomodulatory signaling pathways in macrophages by releasing bacterial cell wall constituents such as peptidoglycan and diconic acid 187 .…”
Section: In Vitromentioning
confidence: 96%
“…Zahlten et al and Herta et al have previously shown that LytA (autolysin) dependent release of bacterial DNA was a controlling factor in the induction of KLF4 in epithelial cells and macrophages during S. pneumoniae infection 167,169 . The present experiment was done to see whether the induction of KLF4 was also dependent on autolysin like in the other cell types.…”
Section: Pneumococci-induced Expression Of Klf4 Depends On Autolysismentioning
confidence: 99%
See 1 more Smart Citation
“…During mycobacterium tuberculosis infection and alcoholic liver disease, upregulation of KLF4 favored M2 polarization. However, Str eptococcus pneumoniae induced KLF4 expression in macrophages, leading to a more proinflammatory macrophage phenotype . In a murine experimental model of autoimmune encephalomyelitis, the increased and sustained expression of KLF4 was found to reduce numbers of proinflammatory T cells and M1 macrophages, as well as to suppress central nervous system inflammation .…”
Section: Introductionmentioning
confidence: 98%
“…However, Streptococcus pneumoniae induced KLF4 expression in macrophages, leading to a more proinflammatory macrophage phenotype. 18 In a murine experimental model of autoimmune encephalomyelitis, the increased and sustained expression of KLF4 was found to reduce numbers of proinflammatory T cells and M1 macrophages, as well as to suppress central nervous system inflammation. 19 23 The mRNA expression of KLF4 remained unaltered in peripheral blood monocytes and macrophages of patients with visceral leishmaniasis.…”
mentioning
confidence: 99%